Competing Claims in Work and Family Life - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2008)
Competing Claims in Work and Family Life, edited by Tanja van der Lippe and Pascale Peters, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Labor Unions; Labor relations; QUALITY of life; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Work life balance